Table-board in daily life of students of the Volhynian Gymnasium and Secondary School in Kremenets - Szmyt, Andrzej (Perspektywa stołu, 2023)
In the Volhynian Gymnasium and Secondary School in Kremenets, which functioned in the years 1805–1831, attention was paid to students’ maintenance. The quality and the sort of nutrition depended on pupils’ wealthiness. The table-board was related to an individual’s living place. Therefore, housing and feeding were diverse. The proper regulations controlled the students’ living conditions. It was necessary to respect them. The mealtimes as well as daily and weekly bill of fare were regulated by school rules. Thanks to students and their parents who resided in Kremenets social life developer there. One of its elements was diverse and very often rich sustenance. It differed from daily feeding. On the basis of bill of fair applicable in boarding schools and vocational schools it is known that table-board was galore, varied and nourishing.